TINGKAH LAKU MELAHIRKAN DAN ESTRUS TIKUS LESOQLATI SULAWESI MAXOMYS HELLWANDII (JENTINK, 1879) - Wahyuni, Indyah (Perhimpunan Biologi Indonesia, 2008)
ABSTRACTParturition Behavior and Estrus of Sulawesi spiny rat Maxomys hellwandii (Jentink, 1879).This research is aimed to study the parturition behavior of wild Sulawesi spiny rat involvingobservations of pre-parturition, parturition and post- parturition behaviors. In this study, 15female white tail rats at the ages of 60 days old were used to evaluate their estrus. Animals weremaintained in cages made of glass at size of 1m x1mx1.5m. The covers of cages were made ofram wire and completed with feeder and drinker. For estrus observation, animal cages weremade of plastic trays of 39 cm x42 cm x15 cm. The phase of estrus cycles observation was doneby collecting sample of vagina smear from the animals. The determination of cycles phase wasbased on the cell types that were obtained from preparation vagina smear. The results showedthat about six hours before parturition, the animals were nervous and urinated 4 to 9 times asthey showed agonistic. The parturition process needed 3 to 8 minutes. The deviation times ofsuckling progeny were 8-12 seconds. The progeny at the ages of 1 to 5 days old slept againsttheir mother nipples. For the estrus, the results showed that estrus cycle of wild white tail ratswas ranging from 3 days to 5 days, consisted of pro estrus (12 hours), estrus (12 hours), metestrus (18 ? 12 hours) and di-estrus (45 - 54 hours).Key Words: Parturition Behavior, Estrus, Maxomys hellwandii.